Psikoedukasi deteksi dini tumbuh kembang anak bagi kader guru - Tri Eka Dewi Puspaningrum (Universitas Muhammadiyah Malang, 2023)
People will go through the stage of growth and development. Growing is associated with increasing size such as weight and height, while developing is related to adding motor, cognitive, emotional and social development skills of individuals. Based on the stages of growth and development, it can be stimulated by environment.In this case, cadres from Raudhatul Athfal (RA) in village X of Malang city had difficulty in distinguishing between children who experienced growth and development according to stages and children who did not match their stages or experienced obstacles. Therefore, to help cadres to be able to distinguish and assist children in stages according to their age, RA cadres will be given education to detect early if there are obstacles in children through psychoeducation early detection of child growth and development. The results of the intervention carried out on RA cadres are increased knowledge related to early detection of child growth and development. They can disseminate this knowledge and continuously apply. Manusia akan melalui tahap pertumbuhan dan perkembangan. Tumbuh dikaitkan dengan bertambahnya ukuran seperti berat badan dan tinggi badan, sedangkan berkembang berkaitan dengan penambahan keterampilan perkembangan motorik, kognitif, emosional dan sosial individu. Berdasarkan tahapan tumbuh kembangnya dapat dirangsang oleh lingkungan. Dalam hal ini, kader Raudhatul Athfal (RA) di desa X kota Malang kesulitan membedakan antara anak yang mengalami tumbuh kembang menurut tahapannya dan anak yang mengalami tumbuh kembang menurut tahapannya. tidak sesuai tahapannya atau mengalami kendala. Oleh karena itu, untuk membantu kader agar mampu membedakan dan mendampingi anak secara bertahap sesuai usianya, maka kader RA akan diberikan edukasi untuk mendeteksi dini jika ada kendala pada anak melalui psikoedukasi deteksi dini tumbuh kembang anak. Hasil intervensi yang dilakukan terhadap kader RA adalah peningkatan pengetahuan terkait deteksi dini tumbuh kembang anak. Mereka bisa menyebarkan ilmu ini dan terus menerapkannya.